Measuring the Effectiveness and Validity of Employees Annual Confidential Report (ACR) and Its Applicability: A Case Study of Abdul Wali Khan University, Mardan - IHTESHAM KHAN; DR. ADNAN AHMAD; DR.SHAHID JAN (Journal of Business & Tourism, 2021)
ACR system is being used as a performance management and evaluation tool in AWKUM for the last five years since its inception as a Public sector university in KPK, Pakistan. The main purpose of this study is to find out that whether ACR system do fulfill the requirement of an effective and efficient Performance evaluation and management tool. What employees think of this system? As any excellent performance management system plays a very vital role in the success of any organization.